2021
DOI: 10.1055/a-1347-5555
|View full text |Cite
|
Sign up to set email alerts
|

Platelets are Hyperactivated but Show Reduced Glycoprotein VI Reactivity in COVID-19 Patients

Abstract: No Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 16 publications
6
44
1
1
Order By: Relevance
“…Thrombocytopenia was found to be associated with disease severity ( 23 26 ) and platelet apoptosis observed in COVID-19 patients requiring intensive care unit treatment ( 27 ). In line with these findings, severely ill COVID-19 patients display elevated markers of platelet activation ( 9 , 26 , 28 30 ) and elevated plasma levels of platelet activation markers ( 31 , 32 ).…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Thrombocytopenia was found to be associated with disease severity ( 23 26 ) and platelet apoptosis observed in COVID-19 patients requiring intensive care unit treatment ( 27 ). In line with these findings, severely ill COVID-19 patients display elevated markers of platelet activation ( 9 , 26 , 28 30 ) and elevated plasma levels of platelet activation markers ( 31 , 32 ).…”
Section: Introductionsupporting
confidence: 68%
“…Thus, the drop of the activated αIIbβ3 complex on platelets of non-surviving COVID-19 patients, observed in the current study, may be attributed to a generally declining amount of total ITGA2B in their platelets due to hyper-activation. Strikingly, it has already been shown that platelets from COVID-19 patients, activated via the GPVI receptor ( 30 , 32 ) show a reduced activation of the integrin-αIIbβ3 complex in comparison to controls. To establish a possible link to our results of diminished ITGA2B in COVID-19, it should be noted that the activation of the integrin αIIbβ3 complex via its altered conformation is quantified by the binding of the antibody PAC-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet hyperactivation in patients with COVID-19 has been reported by several groups [24,25,58,61]. Platelet-leukocyte interactions contribute to the pathophysiology of some viral infections and may play a similar role in SARS-CoV-2 infection.…”
Section: Platelet-leukocyte Interactions In Covid-19mentioning
confidence: 72%
“…In addition, an analysis of blood smears from COVID-19 patients revealed platelet engulfment by lymphocytes [58]. Leopold et al [61] also found higher levels of platelet-neutrophil aggregates in patients hospitalized with COVID-19 (n = 35). In their study of COVID-19 patients within 72 h of ICU admission (n = 35), Hottz et al [24] found higher levels of platelet-monocyte aggregates in ICU patients than asymptomatic/mildly symptomatic patients or healthy controls.…”
Section: Platelet-leukocyte Interactions In Covid-19mentioning
confidence: 96%